Compensatory scaling of modulatory neural populations in response to motor challenges - Tyler L. Wells; Melpomeni Galani; Reynaldo Popoli; Laskaro Zagoraiou; Turgay Akay (Proceedings of the National Academy of Sciences, 2026)
Precise and adaptable movements are achieved by well-regulated muscle contractions, which are mainly governed by the excitability of motor neurons. Several neuromodulatory systems originating in the motor cortex, brainstem, and spinal cord regulate motor neuron excitability via the release of neurotransmitters such as acetylcholine and serotonin. However, these systems can have seemingly similar effects on motor neuron output, raising questions about interaction during movement. To address this, we investigated two modulatory systems in mice: the cholinergic V0c interneurons in the spinal cord and the serotonergic system in the brainstem. Electromyographic and behavioral recordings revealed that, when compared to control mice, mice whose V0c interneuron cholinergic output was genetically inactivated failed to display speed-dependent modulation of the gastrocnemius muscle, and exhibited lower amplitude bursting in the gastrocnemius muscle during swimming. c-Fos expression in this population during locomotion also indicated that they are active in a speed-dependent manner. Relative to control mice, those mice whose V0c interneurons had their cholinergic output inactivated showed upregulated activity in motor-related serotonergic populations while trotting at higher speeds but not while walking at lower speeds, indicating that serotonin plays a compensatory role in the absence of functional V0c interneurons. Last, we observed a progressive recruitment of these two populations in mice with amyotrophic lateral sclerosis, and the recruitment of serotonergic neurons is hastened in those mice whose V0c interneurons had their cholinergic output inactivated. These findings highlight that modulatory systems scale their activity to match motor demand across various circumstances.